New Validated Stability-Indicating Reverse-phase High-performance Liquid Chromatography Method for the Simultaneous Estimation of Prazosin and Polythiazide in their Formulations in Human Plasma - Dharmamoorthy, G. (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: A new simple and precise stability-indicating bioanalytical reverse-phase high-performance liquid chromatography (RP-HPLC) method was developed and validated for the simultaneous estimation of prazosin and polythiazide in their formulation and in human plasma. Materials and Methods: The developed method was successfully used for assaying drug contents in plasma. Isocratic elution mode was carried at Agilent C18 column (150 mm × 4.6 mm, 5 μm particle size) using 0.01 N disodium hydrogen phosphate pH 5.0:acetonitrile (55:45) as mobile phase at flow rate 1.0 ml min at detection wavelength 265 nm. Celecoxib was taken as an internal standard. The method was validated as per ICH guidelines. Results and Discussion: The present validated method can be successfully applied for the estimation of prazosin and polythiazide in human plasma over the concentration range of 12.5–500 ng/m of prazosin and 6.25–250 ng/ml of polythiazide. The method for the determination of prazosin and polythiazide in human plasma using HPLC detection met the acceptance criteria with respect to selectivity, precision, accuracy, linearity, and recovery. Conclusion: The proposed method is simple, rapid, accurate, precise, and appropriate for pharmacokinetic and therapeutic drug monitoring in the clinical laboratories.